Seuils d'inflation et variabilité des prix relatifs dans l'espace CEDEAO - Eunice N. Egbuna; Maimuna John-Sowe; Santigie M. Kargbo; Sani Bawa; Ibrahima Diallo; Isatou Mendy (Institut Monétaire de l'Afrique de l'Ouest (IMAO), 2020)
While the relationship between inflation and relative price variability (RPV) has been widely investigated in developed and emerging market economies because of its direct relevance to monetary policy implementation, research has neglected this linkage in most developing countries especially in the ECOWAS region. This paper examines whether RPV responds differently to different inflation regimes across the ECOWAS region, determining the inflation threshold that would minimize the distortionary impact of expected inflation on RPV in the region. Using the Panel Smooth Transition Regression (PSTR) model over the period 2008:M1 to 2019:M12, the paper finds that ECOWAS countries would achieve lower RPV in the moderate/intermediate inflation regime where the undesirable effect of expected inflation on RPV fades out. This regime ranges from an inflation rate of 7.1 percent to 8.3 percent per annum. The paper further establishes different inflation thresholds for the WAEMU and WAMZ countries, which reflects the differences in inflation tolerance levels between the Zones. It shows that inflation targets below the thresholds of 5.5 percent and 8.3 percent per annum, are desirable in the WAEMU and WAMZ, respectively. Along these lines, this paper concludes that ECOWAS countries should adopt a two-tier inflation compliance regime, until a common monetary policy framework is adopted across the region. The determination of appropriate inflation targets in line with these thresholds in both Zones would pave the way for the adoption of an inflation targeting (IT) regime to anchor inflation expectations and enhance credibility to monetary policy across the wider ECOWAS region.
Keywords: C23; E31; E52; O55; 330; Inflation threshold; relative prices; monetary policy; ECOWAS